2023
DOI: 10.7759/cureus.34914
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence and Management of Chronic Tonsillitis: Experience From Secondary Care Hospitals in Rabak City, Sudan

Abstract: BackgroundTonsillitis is defined as an inflammation of the tonsils, which is a common clinical condition caused by either bacterial or viral infections. It affects a significant percentage of the population especially children. Chronic tonsillitis (CT) is described as when an individual suffers from seven or more attacks of tonsillitis per year. AimThis study aimed to determine the prevalence and management of CT among patients attending all secondary care hospitals in Rabak city, Sudan. MethodsA cross-section… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 13 publications
1
6
0
Order By: Relevance
“…Differences in research results were also obtained in research by Taziki et al(Taziki et al, 2020) in Iran where the highest age group of tonsillectomy patients is the age group of 5-10 years (50.8%). However, this is also in accordance with previous research that says that school age has a high tendency to develop chronic tonsillitis caused by a rudimentary immune system, infections caused by poor ventilation in crowded classrooms, and repeated infections of tonsils that are not treated properly (Alrayah, 2023).…”
supporting
confidence: 92%
See 1 more Smart Citation
“…Differences in research results were also obtained in research by Taziki et al(Taziki et al, 2020) in Iran where the highest age group of tonsillectomy patients is the age group of 5-10 years (50.8%). However, this is also in accordance with previous research that says that school age has a high tendency to develop chronic tonsillitis caused by a rudimentary immune system, infections caused by poor ventilation in crowded classrooms, and repeated infections of tonsils that are not treated properly (Alrayah, 2023).…”
supporting
confidence: 92%
“…(Palandeng et al, 2014) This is in contrast to research on the distribution of chronic tonsillitis patients in Sudan who get the highest number of unemployed or unemployed people who are associated with low socioeconomic status that affects less nutritious food, unhygienic conditions. (Alrayah, 2023)…”
Section: Workmentioning
confidence: 99%
“…The validity of the questionnaire was determined through a panel of (11) The nutritional habits of patients with peptic ulcers for the study group changed after applying the instruction program, which as the mean of means was 1.4 at pre test and improved to 2.3 at post test, than the control group not change at pre and post test, which was 1.5. The result of table (5) revealed that there were statistical significant differences between pretest and post-test for the study group regarding nutritional habits at the P ≤0.05level.As for the control group, there were no statistically significant differences between the pre-and post-test.…”
Section: Methodsmentioning
confidence: 90%
“…The tonsils, enveloped by the tonsillar capsule at the upper end and covered by the palatine arch at the lower end, are lymphoid tissues that play a crucial role in local immune responses [16]. CT in adults refers to the prolonged inflammation of tonsillar tissues, resulting in a chronic inflammatory state [17,18]. Although tonsillar issues are often associated with childhood ailments, adults are equally susceptible to tonsillitis, potentially leading to various otolaryngological complications [19].…”
Section: Discussionmentioning
confidence: 99%